Changing family structures and self-rated health of India's older population (1995-96 to 2014) - Judith Lieber; Lynda Clarke; Ian M. Timæus; Poppy Alice Carson Mallinson; Sanjay Kinra (Elsevier, 2020)
A common view within academia and Indian society is that older Indians are cared for by their families less than in the past. Children are a key source of support in later life and alternatives are limited, therefore declining fertility appears to corroborate this. However, the situation may be more complex. Having many children may be physiologically burdensome for women, sons and daughters have distinct care roles, social trends could affect support provision, and spouses also provide support. We assessed whether the changing structure of families has negatively affected health of the older population using three cross-sectional and nationally representative surveys of India's 60-plus population (1995-96, 2004 and 2014). We described changes in self-rated health and family structure (number of children, sons, and daughters, and marital status) and, using ordinal regression modelling, determined the association between family structure and self-rated health, stratified by survey year and gender. Our results indicate that family structure changes that occurred between 1995-96 and 2014 were largely associated with better health. Though family sizes declined, there were no health gains from having more than two children. In fact, having many children (particularly daughters) was associated with worse health for both men and women. There was some evidence that being sonless or childless was associated with worse health, but it remained rare to not have a son or child. Being currently married was associated with better health and became more common over the inter-survey period. Although our results suggest that demographic trends have not adversely affected health of the older population thus far, we propose that the largest changes in family structure are yet to come. The support available in coming years (and potential health impact) will rely on flexibility of the current system.